Intercultural Learning Critical preparation for international student travel - Jones, Peter; Miles, Debra; Gopalkrishnan, Narayan (Open textbook library., 2019)
Intercultural learning: Critical preparation for international student travel aims to take students beyond practical preparation, to equip them with a critical lens through which to view and understand their international experiences. The book leads students toward a deeper understanding of culture and cultural difference through an exploration of challenging concepts such as imperialism, racism, privilege and intercultural practice. As an adjunct to traditional approaches, the book adds a significant and valuable dimension to the process of preparing students for international study, increasing the potential for meaningful and transformative learning experiences.